Electrocardiogram of secumdum type atrial septal defect simulating endocardial cushion defect. Issue 2 (February 1975) - Tan, K T; Takao, A; Hashimoto, A; Sato, T
Abstract : Three groups of patients are identified in the series of secumdum atrial septal defect with left axis deviation in an analysis of 910 patients of secundum atrial septal defect with or without other accompanying anomalies: 1) 12 patients with isolated ostium secumdum defect; 2) 5 patients with associated prolapse of posterior leaflet of the mitral valve; 3) 4 patients with associated hypertrophic cardiomyopathy and/or single (left) coronary artery. The findings of these 21 patients with proved secumdum atrial septal defect are analysed. The combination of such anomalies should be considered in the differential diagnosis of primum endocardial cushion defect from the electrocardiographic viewpoints.